Τα πρώτα κριτικά - Παλαμάς, Κωστής, 1859-1943 (Λογοτεχνική Βιβλιοθήκη Φέξη, 1913)
Ρήγας Φεραίος -- Διονύσιος Σολωμός -- Ανδρέας Κάλβος -- Γεράσιμος Μαρκοράς -- Ανδρέας Λασκαράτος -- Γεώργιος Καλοσγούρος -- Ιάκωβος Πολυλάς -- Εμμανουήλ Ροΐδης -- Ψυχάρης -- Αλέξανδρος Πάλλης -- Γεώργιος Βιζυηνός -- Ανδρέας Καρκαβίτσας -- Μιχαήλ Μητσάκης